Anti-PGL-1 Positivity as a Risk Marker for the Development of Leprosy among Contacts of Leprosy Cases: Systematic Review and Meta-analysis - Penna, Maria Lucia F.; Penna, Gerson O.; Iglesias, Paula C.; Natal, Sonia; Rodrigues, Laura C. (PLOS Neglected Tropical Diseases, 2016)
Author Summary Contacts of leprosy cases are more likely to be infected and develop leprosy. But not everyone infected with M. Leprae develops clinical leprosy. into clinical disease. We examined and summarized all the eight studies that evaluated how well PGL-1 predicts which contacts of leprosy will become cases. PGL-1 positive contacts were 3 times more likely to develop leprosy; a variable proportion, but less than 30% of the cases were attributed to PGL-1 and less than 45% of the PGL-1 contacts developed leprosy. PGL1 would not be an appropriate test to decide which contacts of leprosy should receive preventive therapy if this was proposed in leprosy control programmes.